Leadership, Human Resource Digitalization, and Performance Assessment on Organizational Performance with Motivational Moderation - Subarjo; Hakim, Lukmanul; M. Hasan Ma'ruf (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of leadership, digitalization of human resource management (HR), and performance appraisal systems on organizational performance with work motivation as a moderation variable. The research was conducted at the Lampung Police Human Resources Bureau involving 100 respondents. Data were collected through questionnaires and analyzed using multiple linear regression and moderated regression analysis (MRA). The results of the study show that leadership, digitization of human resources, and performance appraisal systems have a significant effect on organizational performance. Work motivation has been shown to strengthen the relationship between leadership and human resource digitalization to organizational performance, but does not moderate the relationship between the performance appraisal system and organizational performance. These findings underscore the importance of transformational leadership styles, digitization of human resource management, and a transparent performance appraisal system in improving the effectiveness of public organizations. This research makes theoretical contributions to the human resource management literature as well as practical recommendations for public organizations, particularly in the context of policing. Keywords: Leadership, HR Digitalization, Performance Appraisal, Motivation, Organizational Performance